Виготовлення полотна в селі Кирнасівка на Вінничині (за творами самодіяльного художника Івана Коваля та листами до автора) - Зозуля, Н. (Народна творчість та етнографія, 2007)
On the basis of epistolary heritage of Ivan Koval the author of the article describes a process of linen making in Kyrnasivka village in Vinnytska oblast and investigates main tunes of avocational artist’s creative activity.